Exploring the Pharmacological Potential of Smilax china: Pharmacological Potential of Smilax china (Biological Sciences - PJSIR, 2022)
Smilax china (China root) has been mostly used in conventional medications for the treatment of numerous ailments. In current study, root extracts and fractions of S. china were assessed for antioxidant, flavonoid, phenol contents, antidiabetic (antiglycation, alpha amylase, acetylcholinesterase inhibition), cytotoxicity (DNA protective, hemolytic tests), thrombolysis and antibiofilm efficacies. The methanolic extract was fractionated into n-butanol, n-hexane, chloroform, ethanol, ethyl acetate solvents along with aqueous fraction. Results indicated that n-hexane had maximum DPPH scavenging potential (34%, P